Renal Impairment Detectors: IGFBP-7 and NGAL as Tubular Injury Markers in Multiple Myeloma Patients - Karolina Woziwodzka; Jolanta Małyszko; Ewa Koc-Żórawska; Marcin Żórawski; Paulina Dumnicka; Artur Jurczyszyn; Krzysztof Batko; Paulina Mazur; Małgorzata Banaszkiewicz; Marcin Krzanowski; Paulina Gołasa; Jacek A. Małyszko; et al. (Medicina, 2021)
Background and Objectives: Urine insulin-like growth factor-binding protein 7 (IGFBP-7), tissue inhibitor of matrix metalloproteinase 2 (TIMP-2), and neutrophil gelatinase-associated lipocalin (NGAL) monomer are novel tubular kidney injury biomarkers. In multiple myeloma (MM), immunoglobulin free light chains (FLCs) play an integral role in renal impairment. This study aimed to investigate the correlation between new biomarkers and acclaimed parameters of renal failure, MM stage, and prognosis. Materials and Methods: The examined parameters included: urinary and serum cystatin-C, IGFBP-7, and TIMP-2, and urinary NGAL monomer in 124 enrolled patients. Results: Urinary and serum IGFBP-7 and urinary NGAL were higher among patients with an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2, and positively correlated with urine light chains. Serum and urine IGFBP-7 and urine NGAL were greater among patients with a higher disease stage. In the whole study group, urinary concentrations of the studied markers were positively correlated with each other. In multiple linear regression, urinary IGFBP-7 and NGAL were associated with lower eGFR, independently of other urinary markers. Conclusions: Urinary IGFBP-7 and NGAL monomer may be useful markers of tubular renal damage in patients with MM. Biomarker-based diagnostics may contribute to earlier treatment that may improve renal outcomes and life expectancy in MM.